PERAN ORANG TUA TERHADAP PEMBINAAN KARAKTER ANAK PASCA COVID-19 DI KELURAHAN TASSILILU: Penelitian Skripsi - Andi Annisa; M Hasibuddin; Rosmiati; Abdul Wahab; Muh. Azhar Burhanuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This qualitative study examines the role of parents in character building of children in Tassililu Village, Sinjai Regency, post-COVID-19 pandemic. The results of the study show that although children in Tassililu Village are able to perform religious activities such as praying and reading the Qur'an, and are able to distinguish between good and bad, they still need intensive guidance from their parents in terms of religiosity, discipline, and responsibility. Many children need extra encouragement to carry out their religious activities and duties, and often forget their responsibilities even though they are sometimes able to do homework without being asked. The role of parents as the first and main madrasah for children is very crucial in character building. Parents act as educators, motivators, role models, supervisors, and counselors for their children. Without adequate guidance from parents, children are at risk of having poor or even damaged character. Analysis of supporting and inhibiting factors for character building of children post-COVID-19 in Tassililu Village identified several things. Early habituation, encouragement from parents, and a supportive environment are significant supporting factors. On the other hand, parents' busyness and limited time, the negative influence of digital technology, and a less conducive environment are the main inhibiting factors. This study uses a qualitative method with a case study approach, collecting data through observation, in-depth interviews with parents and children, and documentation. These findings highlight the importance of the active role of parents and the environment in building good character in children, especially in the context of post-COVID-19 pandemic challenges.